6-Methyl-7-deazapurine nucleoside analogues as broad-spectrum antikinetoplastid agents. (December 2021) - Lin, Cai; Hulpia, Fabian; Karalic, Izet; De Schepper, Laurens; Maes, Louis; Caljon, Guy; Van Calenbergh, Serge
Abstract: Kinetoplastid parasites are the causative agents of Chagas disease (CD), leishmaniasis and human African trypanosomiasis (HAT). Despite a sustained decrease in the number of HAT cases, more efforts are needed to discover safe and effective therapies against CD and leishmaniasis. Kinetoplastid parasites lack the capability to biosynthesize purines de novo and thus critically depend on uptake and processing of purines from host cells. As such, modified purine nucleoside analogues may act as broad-spectrum antikinetoplastid agents. This study assessed the in vitro activity profile of 7-modified 6-methyl tubercidin derivatives against Trypanosoma cruzi, Leishmania infantum, Trypanosoma brucei brucei and T. b. rhodesiense, and led to the identification of analogues that display activity against all these species, such as 7-ethyl (13 ) and 7-chloro (7 ) analogues. These selected analogues also proved sufficiently stable in liver microsomes to warrant in vivo follow-up evaluation. Graphical abstract: Image 1 Highlights: New safe and effective therapies are needed for Chagas disease and leishmaniasis. The causative agents rely on the acquisition of purine nucleobases and nucleosides from host cells to grow and multiply. New 7-substituted 6-methyl-7-deazapurine ribonucleosides were synthesized . A 7-ethyl and 7-chloro analogue display low to submicromolar activity against T. brucei, T. cruzi and L. infantum .